From Fixed to Float Operational Aspects of Moving towards Exchange Rate Flexibility - Fernandez, Gilda (International Monetary Fund, 2004)
This paper identifies the institutional and operational requisites for transitions to floating exchange rate regimes. In particular, it explores key issues underlying the transition, including developing a deep and liquid foreign exchange market, formulating intervention policies consistent with the new regime, establishing an alternative nominal anchor in the context of a new monetary policy framework, and building the capacity of market participants to manage exchange rate risks and of supervisory authorities to regulate and monitor them. It also assesses the factors that influence the pace of exit and the appropriate sequencing of exchange rate flexibility and capital account liberalization